Analisis Pasang Surut Di Pantai Dumai Menggunakan Metode Least Square 15 Piantan - Arif, Muhammad; Hendri, Andy; Suprayogi, Imam (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Least square is a method of tidal harmonic analysis that ignores meteorological factors in analyzing and predicting tidal elevations. This study analyzes the accuracy of tidal elevation predictions based on the initial date of the simulation. The analysis used 15 days tidal data from Pelindo Port C, Dumai. Furthermore, the results of the study were compared with the results of the most recent study, namely predictions of tide admiralty 15 days in the same location. The results of this study indicate that the results of the 15 days least square method prediction are more accurate than the admiralty method. The RMSE value from the least square method calculation gives the smallest Root Mean Square (RMSE) value of 34,56 cm, while the admiralty method is 71,38 cm. The most appropriate time to take primary data in the field for the purposes of tidal predictions is at the beginning of the third week of each month in the hijri calender or when the half moon phase.Keywords : least square method, tidal prediction, RMSE